2021
DOI: 10.1002/adhm.202100031
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton‐Guided Creation of Complex Organ‐Specific Microvasculature

Abstract: Engineering functional human tissues in vitro is currently limited by difficulty replicating the small caliber, complex connectivity, cellularity, and 3D curvature of the native microvasculature. Multiphoton ablation has emerged as a promising technique for fabrication of microvascular structures with high resolution and full 3D control, but cellularization and perfusion of complex capillary-scale structures has remained challenging. Here, multiphoton ablation combined with guided endothelial cell growth from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…An additional breakthrough is the recent work by the Zheng group [ 123 ], in which multiphoton ablation is used to create perfusable micro-vessels at anatomic scale within collagen hydrogels. By seeding them with endothelial cells, the authors created cellularized, organ-specific microvascular structures, such as 3D pulmonary and renal microvascular beds.…”
Section: Laser-fabricated Active Microstructured Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional breakthrough is the recent work by the Zheng group [ 123 ], in which multiphoton ablation is used to create perfusable micro-vessels at anatomic scale within collagen hydrogels. By seeding them with endothelial cells, the authors created cellularized, organ-specific microvascular structures, such as 3D pulmonary and renal microvascular beds.…”
Section: Laser-fabricated Active Microstructured Hydrogelsmentioning
confidence: 99%
“…In this latter case, successful blood perfusion of a kidney-specific microvascular structure was achieved ( Figure 9 B). In the work by Zheng et al [ 123 ], it is particularly interesting to note the evaluation of the ablation characteristics of three materials among the most commonly used for tissue engineering: collagen (7.5 ), fibrin (10 ), and a hydrogel containing 2% ( w / v ) each of agarose and gelatin. Channels were laser-ablated with laser powers in the range 107 mW 244 mW and 800 nm between two reservoirs formed lithographically within collagen or fibrin hydrogels.…”
Section: Laser-fabricated Active Microstructured Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the glomerulus in situ has a complex structure with intricate microvascular capillary networks in a unique geometry that could play a role in the development and function of podocytes ( Falkenberg et al, 2017 ), there have been significant efforts to generate 3D models with complex microvascular networks using 3D bioprinting technology. Rayner et al demonstrated the use of a multiphoton microscopy-guided 3D printing technique to generate perfusable vascular networks with diameters as small as 10 μm ( Rayner et al, 2021 ). They further demonstrate bioprinting of a glomerular-like microvascular network that supports endothelial lumen formation; however, they still require the incorporation of podocytes and mesangial cells to recapitulate the glomerular physiology and to study cell-cell crosstalk.…”
Section: Studying Glomerular Cell Crosstalkmentioning
confidence: 99%
“…Although many key functional features of complex organ systems can be replicated with organ-on-a-chip systems, the physical constraints of plastic microchannels and membranes in these closed microfluidic devices limit the structural design of the tissue microenvironment that can be engineered. To integrate perfusion and complex 3D tissue structures, microfluidic chips could be pre-fabricated, and perfusable networks can be subsequently introduced in the chip with a 3D laser beam microdissection technique [8][9][10] . While this technique is powerful and produces high-resolution features, it can be slow and difficult to scale.…”
Section: Introductionmentioning
confidence: 99%